The role of tectonics in geopressure compartmentalisation and hydrocarbon leakage in the deep offshore Niger Delta - Nosike, L.; Wibberley, C.; Jardiné, C.; Pacalin, Y. (TRABAJOS DE GEOLOGÍA, 2010)
The Niger Delta’s deformation regime, controlled by NE-SW gravitational tectonics, formsimbricate thrust structures in the deep offshore, and generates profuse fluid expulsions expressed aspockmarks ±700 m and mud volcanoes ±2800 m in diameter. Gravity loading by sediment alone is notsufficient to explain the expulsions, and their classified morphology and proximity to the folds suggesta link with the structural compartmentalisation and pressure distributions. This work used 3D-seismicand well-data to link the leakages to active and inactive tectonic processes, highlighting the role of mainand subsidiary faults and changing stress regimes before suggesting a “layer-by-layer” behaviour toexplain the vertical and lateral geopressure compartmentalisation.